Relationship between Cooperative learning method and Students’ Mathematics Learning Achievement: A Meta-Analysis Correlation - Setiana, Dafid Slamet; Ili, La; Rumasoreng, Muhammad Irfan; Prabowo, Anggit (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
An appropriate learning method can improve students’ learning achievement. The cooperative learning method encourages students to improve their mathematics learning achievement. Mathematics learning achievement is one indicator of achieving learning objectives. Mathematics is an important lesson to be learned and must be mastered by students. The purpose of this research was to analyze the effect size of the relationship between Cooperative learning method and mathematics learning achievement through meta-analysis quantitative research approach. In this research, the cooperative learning method serves as an independent variable, and mathematics learning achievement serves as the dependent variable. The data was obtained from the online database search results on Google Scholar in 2010-2020. The sample used was 16 research publications that have met the specified criteria. The data analysis technique used was the meta-analysis quantitative approach with correlation meta-analysis. The results showed that there was a positive and significant relationship (level of 5%) between the cooperative learning method and students’ mathematics learning achievement. The average effect size value was 0.15 in the range of 0.04 to 0.27 which was included in the low category. These results have proven the consistency of the findings of previous research.